2013
DOI: 10.1103/physreve.87.023004
|View full text |Cite
|
Sign up to set email alerts
|

Mean scalar concentration profile in a sheared and thermally stratified atmospheric surface layer

Abstract: Using only dimensional considerations, Monin and Obukhov proposed a 'universal' stability correction function φc(ζ) that accounts for distortions caused by thermal stratification to the mean scalar concentration profile in the atmospheric surface layer when the flow is stationary, planar homogeneous, fully turbulent, and lacking any subsidence. For nearly six decades, their analysis provided the basic framework for almost all operational models and data interpretation in the lower atmosphere. However, the cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…This flux-profile relation showed a better agreement with the corresponding f C T 2 functions. More recently, Katul et al (2011Katul et al ( , 2013) proposed flux-profile relations that account for anisotropy, advection and pressure fluctuations, which could in the same way give better correspondence with the MOST relations shown here. Figure 2 has the same set-up as Fig.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This flux-profile relation showed a better agreement with the corresponding f C T 2 functions. More recently, Katul et al (2011Katul et al ( , 2013) proposed flux-profile relations that account for anisotropy, advection and pressure fluctuations, which could in the same way give better correspondence with the MOST relations shown here. Figure 2 has the same set-up as Fig.…”
mentioning
confidence: 64%
“…Also for f C q 2 under stable conditions the flux-profile-derived function deviates from the function found herein. This difference may again be related to the fact that intermittent turbulence (Beljaars and Holtslag 1991), or anisotropy, advection and pressure fluctuations (Katul et al 2011(Katul et al , 2013 are missing mechanisms in the flux-profile relations as we described in Sect. 4.1.…”
Section: Fig 2 Most Functions Of C Qmentioning
confidence: 99%
“…There was a significant difference (p<0.01) in mean S 0 between sites every year, with sweeps more prominent in momentum transport at KON and ejecting motions from the canopy tending to be more dominant at K4B. Some studies have shown that S 0 is higher with denser canopies (Katul et al, 2006(Katul et al, , 2013, which would lead to an expectation of increasing S 0 seasonally and higher S 0 values at K4B, where LAI tends to be higher. However, results for momentum show the opposite, with S 0 steadily lower at K4B and tending to decrease slightly over the growing season, corresponding to increased ejections from the canopy with greater canopy density.…”
Section: Changes In Turbulent Dynamicsmentioning
confidence: 82%
“…In the surface layer, the dominant motion depends on stability and canopy conditions. Under neutral conditions, sweeps and ejections are typically balanced, while under unstable conditions ejections dominate over sparse canopies and sweeps dominate over denser canopies (Katul et al, 2006(Katul et al, , 2013. It is hypothesized that the ratio of sweeps and ejections will differ between a stable grassland and one experiencing significant woody encroachment with sweeps becoming more prominent with the resultant changes in canopy composition.…”
Section: Introductionmentioning
confidence: 98%
“…While these flux-gradient relationships are assumed to be universal, the exact functional forms of these relationships cannot be predicted by MOST (Stull 1988;Foken 2008). There have been new studies exploring the functional forms of these flux-gradient relationships from a theoretical perspective (Katul et al 2011(Katul et al , 2013Li et al 2012b), which still rely significantly on experimental observations. The functional forms of these flux-gradient relationships have been the topic of many field campaigns, including the famous Kansas experiment (Dyer and Hicks 1970;Businger et al 1971) over land and the Coupled Ocean-Atmosphere Response Experiment (COARE) (Fairall et al 1996(Fairall et al , 2003 over ocean.…”
Section: Introductionmentioning
confidence: 99%